u-Deformed WZW model and its gauging - Klimčík, C. (Symmetry, Integrability and Geometry: Methods and Applications, 2006)
We review the description of a particular deformation of the WZW model. The resulting theory exhibits a Poisson-Lie symmetry with a non-Abelian cosymmetry group and can be vectorially gauged.